The Social Representation of Feminism within the On-line Movement “Women Against Feminism” - Oana Crusmac (Romanian Journal of Communications and Public Relations, 2017)
The present paper aims to analyse the social representation of feminism within the “Women Against Feminism” (WAF) on-line movement that is based on a shared blog which gained significant coverage in the U.S. and U.K. media since the summer of 2014. Using the method of quantitative content analysis and the insights provided by social representations theory, the paper will disclose what lies behind the concept of ‘feminism’ for the group embracing the WAF movement and also aims to find whether the members of this on-line community can be described as postfeminists. The article will conclude that the social representation of feminism within the WAF on-line movement is not based on a lack of information, but rather on a stereotypical understanding of the concept and on a non-nuanced perspective upon the history of feminism and its current developments (in particular the difference between post-feminism and third wave feminism). Moreover, similar arguments raised against feminism have been also drawn in the past, WAF sharing similar arguments with the ‘80s media backlash against feminsim.